Right ventricular dyssynchrony and exercise capacity in idiopathic pulmonary arterial hypertension. Issue 6 (1st June 2017) - Badagliacca, Roberto; Papa, Silvia; Valli, Gabriele; Pezzuto, Beatrice; Poscia, Roberto; Reali, Manuela; Manzi, Giovanna; Giannetta, Elisa; Berardi, Daniele; Sciomer, Susanna; Palange, Paolo; Fedele, Francesco; et al.
Survival in patients with pulmonary arterial hypertension (PAH) is determined by right ventricular (RV) function adaptation to afterload. How altered RV function impacts on exercise capacity in PAH is not exactly known. 104 idiopathic PAH (IPAH) patients aged 52±14 years underwent a diagnostic right heart catheterisation, a comprehensive echocardiography including two-dimensional speckle tracking for RV dyssynchrony evaluation and a cardiopulmonary exercise test. Multivariate analyses were performed to identify independent predictors of peak oxygen uptake (peak V ′O2 ). A first multivariate analysis of only resting haemodynamic variables identified cardiac index, right atrial (RA) pressure and pulmonary arterial compliance as independent predictors, with low predictive capacity (r 2 =0.31; p<0.001). A second multivariate analysis model which considered only echocardiographic parameters but without RV dyssynchrony, identified RV fractional area change (FAC) and RA area as independent predictors with still low predictivity (r 2 =0.35; p<0.001). Adding RV dyssynchrony to the second model increased its predictivity (r 2 =0.48; p<0.001). Repetition of the three multivariate analyses in patients with preserved RVFAC confirmed that inclusion of RV dyssynchrony results in the highest predictive capability of peak V ′O2 (r 2 =0.53; p=0.001). A comprehensive echocardiography with speckle tracking-derived assessment of the heterogeneity of RV contraction improves the prediction of aerobic exercise capacity in IPAH. Speckle tracking assessment of RV dyssynchrony improves the prediction of aerobic exercise capacity in IPAH http://ow.ly/yHyh30bedtD